Analisa Pembayaran Berbicara Dalam Konteks Pendidikan - Seyla Putri Rizkyta (Journal Of Language Education and Development (JLed), 2022)
This article analyses the importance of learning to speak in an educational context. Speaking learning plays an important role in developing students' communication skills. In this analysis, the author explores various methods and strategies that can be used to improve students' speaking skills in the classroom. The results of the analysis show that effective speaking learning requires a comprehensive approach, including the use of technology, simulations, and active student roles in discussions and presentations. This article provides valuable information for educators to plan and implement effective oral teaching. The importance of learning to speak in an educational context is beyond doubt. Good speaking skills are essential in everyday life, both in social settings and the world of work. In this article, the author attempts to analyse in depth the strategies and methods that can be used to improve students' speaking skills in the classroom. One of the main conclusions of this analysis is that learning to speak effectively requires a comprehensive approach. This means that it does not only focus on developing technical speaking skills but also involves the use of technology, simulation and the active role of students in discussions and presentations. In today's digital era, the use of technology to learn speaking is very relevant. Therefore, the author emphasises the importance of integrating technology into the learning of verbal expression so that students become familiar with technology and develop speaking skills more effectively.